Does International Law Regulate Relations with Participation of Individuals? (Part I) - B. I. Nefedov (Московский журнал международного права, 2017)
The оccurrence and the futility of the scientific debate on the most debated in the scientificliterature of the fundamental problems of the General theory of international law related to same – lack of resolution of complex theoretical problems, which can be called the main problem of the theory of international law over the past century and a half. It is based on seemingly irreconcilable differences. So, on the one hand, international legal norms can (under certain conditions) regulate relations with participation of individuals but, on the other hand, individuals are subjects of international law and relations involving them are not international intergovernmental relations, i.e. subject to international law. In the first part the article provides a criticism of the main directions taken in science attempts to solve this problem: theories of transformation; concepts recognition relationships with participation of individuals regulated by norms of international law, international relations; concepts of international legal personality of individuals; claims that Private international law does not have its own content, and represents only teaching and/or scientific term. In the result it is concluded that none of these concepts does not solve the basic problem of the General theory of international law. In the second part of the article offers the solution.